Argument Structure in Flux : the Naples-Capri Papers - Gelderen, Elly van; Cennamo, Michela; Jóhanna Barðdal, 1969- (Studies in language companion series, 2013)
In this paper we claim that the emergence of the existential pro-form in early Italo-Romance is motivated by the overt marking of definiteness on the pivot. The available data from a relatively large corpus of early Italo-Romance texts dating from C13th to C16th suggest that the overt marking of definiteness, which differentiates Romance from its ancestor Latin, favours the establishment of an existential pattern where the encoding of non-canonical pivots (definite ones) is licensed only if a locative element occurs in the structure; this can be a locative phrase, a locative relative pronoun o.